Tipos de comportamiento según la escala de Frankl presentados en pacientes odontológicos - Argüello-Ramos, Edison David; Pillco-Chicaiza, Joselyn Giomaira; Pancho-Chavarrea, Tatiana Lucrecia (Revista Arbitrada Interdisciplinaria de Ciencias de la Salud. Salud y Vida, 2022)
Objective: To determine the types of behaviors using a survey using the Frankl scale in pediatric patients who have been seen in the pediatric dentistry clinic of the "UNIANDES" Dental Care Unit during the period 2019-2020 corresponding to the ninth and tenth semesters in order to establish the most frequent and periodic behavior in dental care. Method: A cross-sectional, descriptive study was carried out. Results: An incidence of 54.90% of children with "Slightly Positive" behavior according to the Frankl scale and only 18.30% "Slightly Negative" during dental care at the "Uniandes" Dental Care Unit was demonstrated. Conclusions: Thanks to Frankl’s scale it is possible to define the type of behavior and choose the best procedure for a pleasant attention to each patient.